Two new species of genus Spilolonchoptera Yang, 1998 from China (Diptera, Lonchopteridae) - Gao, Shang; Zhang, Bing; Yang, Ding (Zootaxa, 2021)
Only five species of the genus Spilolonchoptera Yang, 1998 were previously known from China. Here two new species, Spilolonchoptera hainanensis sp. nov. and Spilolonchoptera zhejiangensis sp. nov. are reported from China. A key to species of the genus Spilolonchoptera from China is presented.